The Role of Diaphragmatic Ultrasound in Identifying Sarcopenia in COPD Patients: A Cross-Sectional Study - Yetkin NA; Akın S; Kocaslan D; Baran B; Rabahoglu B; Oymak FS; Tutar N; Gulmez İ (International Journal of COPD)
Nur Aleyna Yetkin,1 Sibel Akın,2 Derya Kocaslan,2 Burcu Baran,1 Bilal Rabahoglu,1 Fatma Sema Oymak,1 Nuri Tutar,1 İnci Gulmez1 1Pulmonology Department, Erciyes University Faculty of Medicine, Kayseri, Türkiye; 2Geriatrics Division, Internal Medical Sciences Department, Erciyes University Faculty of Medicine, Kayseri, TürkiyeCorrespondence: Nur Aleyna Yetkin, Email alleynakemik@gmail.com, nuryetkin@erciyes.edu.trBackground/Aim: Chronic obstructive pulmonary disease (COPD) is often complicated by sarcopenia, a condition of reduced muscle mass and function that adversely affects quality of life, lung function, and exacerbation rates. Ultrasonography could be an effective tool for detecting sarcopenia, notably by assessing diaphragmatic function, which may indicate muscle health in COPD patients. This study aims to evaluate the effectiveness of diaphragmatic ultrasound in detecting sarcopenia among COPD patients.Materials and Methods: Thirty-five patients with COPD, with a forced expiratory volume in one second (FEV1) between 30% and 80%, were consecutively enrolled in this cross-sectional and double-blind study. Sarcopenia was defined using the European Working Group on Sarcopenia in Older People 2 (EWGSOP2) criteria. Muscle mass was assessed with bioelectrical impedance analysis (BIA), muscle strength was assessed using the handgrip test and physical performance was assessed using a 4-meter gait speed test. Pulmonary function tests (PFT) (including maximum inspiratory pressure-MIP and maximum expiratory pressure-MEP) were performed. Diaphragm excursion and thickness at residual volume, functional residual capacity, and total lung capacity were measured using ultrasound. The diaphragm thickening fraction was calculated during normal (TF) and deep breathing (TLC-TF).Results: Seventeen of 35 patients (48.6%) were found to be sarcopenic. Diaphragm thickness did not show significant variation between the groups. Both TF (27.43%) and TLC-TF (39.7%) were found to be lower in the sarcopenic group (p< 0.05). The diaphragmatic excursion in the sarcopenic group was found to be 1.38 cm (p=0.078). There was no difference in median MIP and MEP values between the groups.Conclusion: Diaphragmatic TF may be a valuable tool for detecting sarcopenia in COPD patients, which may vary independently of PFTs. This study highlights TF as a potential auxiliary measure, but further research with larger sample sizes and additional parameters is needed to confirm its clinical utility.Keywords: excursion, frailty, obesity, respiratory failure, FEV1